Could a Dolutegravir-Based Antiretroviral Therapy Lead to Clinical Obesity? A Retrospective Cohort Study Conducted at Hawassa University Comprehensive Specialized Hospital in Hawassa, Sidama, Ethiopia. (13th May 2022) - Eifa, By Aberash; Ketema, Worku
Abstract : Background . As of April 2019, the dolutegravir (DTG)-based regimen is replacing the efavirenz-based regimen in Ethiopia, mainly due to its superiority in viral load suppression. However, there is a growing concern about this medication-based regimen, the most serious of which is excessive weight gain. In this study, we looked at weight gain disparities among human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) patients on antiretroviral therapy (ART) who have been shifted to tenofovir/lamivudine/dolutegravir (TLD) from a tenofovir/lamivudine/efavirenz (TLE)-based regimen versus those who are maintained on a tenofovir/lamivudine/efavirenz-based regimen. Methods . A facility-based retrospective observational cohort study was conducted in pursuit of weight change disparities between tenofovir/lamivudine/dolutegravir and tenofovir/lamivudine/efavirenz-based regimens among patients who have attained optimal viral suppression at Hawassa University Comprehensive Specialized Hospital antiretroviral clinic. Chi-square and logistic regression were used as appropriate using an SPSS version 21 program to test the association of specific variables to outcome variables, and a P value <0.05 was considered statistically significant. Results . This study included 422 patients, 211 of whom were switched from tenofovir/lamivudine/efavirenz to tenofovir/lamivudine/dolutegravir and the remaining were who kept on a tenofovir/lamivudine/efavirenz-based regimen. Patients on a tenofovir/lamivudine/dolutegravir-based regimen had a mean weight gain of 3.88 ± 2.021 kg in one year compared to those on TLE (2.26 ± 2.39). In a bivariate analysis, being male was found to protect against unwanted weight gain at COR 0.531 (0.345, 0.816). A current CD4 count of more than 500 has been found to be strongly correlated with weight gain in multivariate analysis at an AOR of 0.315 (0.188, 0.527) at a P value ≤0.001. Conclusion . According to this study, tenofovir/lamivudine/dolutegravir (TLD)-based antiretroviral medication (ART) users are more likely to gain weight, and clinicians should advise them of the risks of weight gain as well as cost-effective ways to prevent weight gain linked to poor health outcomes in these patients. Future investigations should confirm the findings of this study, and more research into the effects of weight gain in these people is required.